The feeding of infants and children - Krut, A. S.; Ivanko, O. G.; Kizima, N. V.; Paschenko, I. V.; Pidkova, V. Y.; Radutna, O. A.; Круть, Олександра Степанівна; Іванько, Олег Григорович; Кизима, Наталя Володимирівна; Пащенко, Ірина Володимирівна; Підкова, Віра Ярославівна; Радутна, Олена Анатоліївна (Zaporizhzhya state medical university, 2013)
The handbook can be used by teachers and students at practical classes and for module control 3 “The feeding of infants and children” in the discipline “Propedeutics of Pediatrics”. The content of the handbook corresponds to the requirements of “Educational qualification characteristics of the specialist in specialty 7.120101 “General Medicine”.